A Study Of The Antigenicity Of Salmonella Enterica Subspecies Enterica Serovar Typhi 50 Kda Recombinant Proteins - Teh Boon, Aun (2018)
S. Typhi 50 kDa outer-membrane protein (OMP) was reported to be antigenic and has been used to develop the commercially successful Typhidot® kit. However, the specificity of the kit varies from 37.5 to 98.8%. This might be due to contamination with other proteins during the 50 kDa OMP preparation and it could have affected the specificity of the 50 kDa OMP. The objective of this study was to investigate the identities of the individual proteins contained in the 50 kDa protein complex to pinpoint the immunodominant protein(s) responsible for its antigenicity, and thus improve the sensitivity and specificity of the Typhidot® test. 2D-gel electrophoresis and LC-MS/MS were used to identify the proteins in the complex. From the pool of identified proteins, TolC, GlpK, FliC and SucB were identified as potential antigenic proteins in the 50 kDa OMP complex and recombinant proteins were produced in E. coli. Due to the insoluble nature of the proteins, purification was carried out using native and denaturing conditions to improve the yield of soluble recombinant proteins. The ELISA results showed that recombinant GlpK (rGlpK) and recombinant FliC (rFliC) against pooled typhoid sera have the highest absorbance reading, while recombinant TolC (rTolC) and recombinant SucB (rSucB) showed low absorbance reading. The ELISA results also showed that the antibodies reacted stronger with the rGlpK and rFliC proteins when there were purified under native condition. This suggested the presence of linear and conformational epitopes on these proteins. However these two proteins were found to be unsuitable as biomarkers due to non-specific binding with pooled normal serum and rFliC protein cross-reacted with antibodies in sera of subjects infected with other Salmonella and non-Salmonella serovars.